A onipresença das competências na formação docente: um estudo no horizonte da reificação e do reconhecimento - Fagundes, André Luiz de Oliveira (2013)
The main guiding proposal of this paper aims to answer the following questions: In which way the official legislation of the teaching formation (allusive to the school teachers) based on the conceptions of competences contributes to the manifestation of reification, as its fundamental proposals surround centrally around of the know-do (Savoir-faire), leaving aside other fundamental aspects of the human formation, in a indiscriminate search for the practice? How can a change be taught on the perspective of intersubjective recognition? Thereby, the work in question is situated on the Philosophy of Education perspective, having as theoretical reference the contribution of the studies about reification and social recognition, from Axel Honneth, recognized member of the called third generation of the Frankfurt School. The general scope of the research is to perform an analysis of the philosophical implications referring to the political and epistemological content of the last renovation on the educational field. In more specific terms, our objectives are: a) conduct a critical analysis, based on the category of the reification, from the principles of the competences directed to the educational field by the legislation; b) elucidate the existing relations between claim of the practice on the instructor formation and the possible manifestations of reification in the educative process; c) measure the relation of the legacy of the reification category for the comprehension of the school teaching formation problem; d) study the possibilities to present proposals for the teaching formation inspired on the idea of recognition of the other, counterposed to reifying situations and non-recognition experiences. To do so, we followed as methodological orientation the hermeneutical spin of the critical theory .